Analisis Ketahanan Pangan Kota Bandung Berdasarkan Peta FSVA Tahun 2023 - Eka Purna Yudha; Riska Riska; Futri Fauza Fadillah; Hersya Nuriska Anandita; Biru Angeli Nirwana (Universitas Galuh, 2026)
Food security is a strategic issue in urban development, particularly in Bandung, which has a high population density. This study aims to analyze the condition of food security and vulnerability in Bandung City based on the 2023 Food Security and Vulnerability Atlas (FSVA) using a quantitative descriptive approach. The analysis was conducted on three dimensions of food security: food availability, access, and utilization, through indicators of land and agricultural production, food supply facilities, population welfare, transportation access, clean water access, and the ratio of health workers. The results show that Bandung City is highly dependent on food supplies from outside the region due to limited agricultural land and the low contribution of the agricultural sector. Although most urban villages are classified as food secure, there are still low to moderately vulnerable villages affected by unequal access to clean water, limited health workers, and low-income populations. This study emphasizes the importance of strengthening sustainable, region-based food security policies.